Prevenção da violência escolar na perspectiva de diferentes atores: uma proposta de prevenção - Silva, Shirlei de Matos da (2024)
School violence reflects a society that has normalized violent acts.The increase in attacks on students, teachers and school staff in various regions of Brazil highlights this worrying trend. Violent conflicts in the school context have intensified, occurring between students, between students and teachers, among teachers themselves, and among other staff members. The school, originally conceived as an environment for socialization and the formation of individuals, a space of influence, safety and protection, has become a source of fear and uncertainty for many. It is necessary to address violence as a multifaceted phenomenon that can generate numerous negative impacts on both student development and teachers. It is crucial to seek ways of dialogue, prevention, and combating violence in the school context. This research aimed to develop an intervention program to prevent school violence, considering suggestions from parents and guardians, teachers, and students in distinct groups. This is a descriptive and exploratory study with a qualitative approach. Data collection was carried out through subjective interviews using the Focus Group research technique, involving groups of parents and guardians, students, and teachers from five municipal elementary schools in Foz do Iguaçu, Paraná, randomly selected from different regions of the city. The data were analyzed using Discursive Textual Analysis. The results point to several preventive measures that schools can adopt to prevent school violence, including the implementation of emotional education programs, the promotion of dialogue and conflict resolution, as well as the active involvement of teachers and other staff members in monitoring and preventing violence. Additionally, the need for public policies that address security, leisure, and therapeutic support for children and families affected by violence is emphasized. Based on the analyzed data, a proposal for an intervention program for municipal schools was developed from the perspective of their stakeholders. We understand school violence as a widespread problem that affects entire society, and its prevention requires joint efforts. Collaboration between the school, family, and community, along with the implementation of public policies that prioritize safety, is essential to prevent school violence. Expanding knowledge about school violence and implementing comprehensive policies are essential steps to create a school culture based on respect and cooperation, restructuring schools into places of academic learning and comprehensive human development.